Naringin Mediated Silver Nanoparticles Attenuate Rheumatoid Arthritis in Mice by Modulation of Autophagy and PI3K/AKT/mTOR Signaling Pathway - Ekta Yadav (Journal of Clinical Rheumatology and Immunology)
Background: Rheumatoid arthritis (RA) is characterized as an autoimmune inflammatory disease associated with synovial joints. Naringin (NG) is a flavanone type of glycoside found in grapes and citrus fruits, and reported to be active against RA. However, poor bioavailability and low solubility restricted its clinical use. Therefore, considering the issue, the present study was focused on the development, characterization and exploration of the protective efficacy of naringin-mediated silver nanoparticles (AgNNPs) against RA by using in vitro and in vivo methods. Methods: AgNNPs were biosynthesized by co-precipitation approach and characterized by different techniques. Biofabricated AgNNPs were employed to analyze the anti-arthritic effects by using an in vivo mouse model, i.e., type II collagen-induced arthritis (CIA) model and various parameters including degree of paw swelling, polyarthritis index score as well as level of cytokines in serum were evaluated. The effect of AgNNPs on the proliferation level of fibroblast-like synoviocytes (FLS) induced by tumor necrosis factor-[Formula: see text](TNF-[Formula: see text]) was also taken into account. Western blot and immunofluorescence staining were employed to detect the status of autophagy and underlying PI3K/AKT/mTOR pathway in the CIA model and FLSs. Results: Various characterization techniques confirmed the formation of spherical crystalline nanoparticles with a size range of 40-80 nm. In vivo study results revealed that AgNNPs significantly reduced (P < 0.01) the RA-associated damaging effects such as level of paw edema, and pro-inflammatory cytokines along with inhibition of FLSs proliferation associated with TNF-[Formula: see text]. Level of autophagosome and protein expression of LC3B in TNF-[Formula: see text]induced FLSs, LC3-II and Beclin-1 were enhanced whereas mTOR and AKT phosphorylation were reduced by AgNNPs treatment. Conclusion: The study exhibited an ameliorative effect of biosynthesized AgNNPs against RA by modulating autophagy through PI3K/AKT/mTOR signaling pathway.